2006
DOI: 10.1177/105382590602900208
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of an Outdoor Adventure Education Curriculum on Selected Aspects of Positive Psychological Development

Abstract: To date, little empirical research has been conducted to support the claim that outdoor adventure education (OAE) develops desirable psychological characteristics in participants. This study examined the effects of an OAE foundation degree curriculum on positive psychological development. Fifty-two students (26 OAE students, 26 controls on an unrelated course), aged 16–39 years, completed a battery of positive psychological questionnaires (at the start of their respective courses and 3 months later) measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 66 publications
3
46
2
4
Order By: Relevance
“…Several studies have evaluated the effect of ODA on global self-esteem, with mixed results. Sheard and Golby (2006) conducted a study with English college students aged between 16 and 39 years. The experimental group (n = 26) were students on a two-year Outdoor Adventure Education (OAE) foundation degree course.…”
mentioning
confidence: 99%
“…Several studies have evaluated the effect of ODA on global self-esteem, with mixed results. Sheard and Golby (2006) conducted a study with English college students aged between 16 and 39 years. The experimental group (n = 26) were students on a two-year Outdoor Adventure Education (OAE) foundation degree course.…”
mentioning
confidence: 99%
“…It has also been reported that such kind of activities move participants out of their comfort zone within the framework of perceived risk and provide personal development by feeding qualities such as cooperation, perseverance, determination, persistence, resistance, problem solving etc (Çelebi and Özen, 2004;Sheard and Golby, 2006) as well as provide competences such as perseverance of struggling etc. that can be used in real life (Neill, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, it is specified that various experiences such as rock climbing, canoe, camp activities etc feed certain qualifications like entrepreneurship, cooperation, perseverance, determination, persistence, resistance, problem solving etc. (Çelebi and Özen, 2004;Sheard and Golby, 2006). Considering all this information, it is possible to say that artificial wall climbing activity carried out in our study begets a positive development on participants' problem solving perception.…”
mentioning
confidence: 90%
“…Previous research found increased identity development as well as growth in interpersonal skills and positive self-schema among students who participate in outdoor adventure programs (Russell, 2003;Sibthorp & Morgan, 2011;Sibthorp, Paisley, Gookin, & Furman, 2008). OB specifically has been found to contribute significantly to building skills needed for successful relationship development, such as emotional self-efficacy, (Sheard & Golby, 2006) as well as improved communication and reflective thinking (Fleming & Eames, 2005).…”
Section: The Role Of Outdoor Education Programmingmentioning
confidence: 99%